Evaluation of a Semantic-Oriented Approach to Cross-Lingual Ontology Mapping - BRENNAN, ROB; O'SULLIVAN, DECLAN; FU, BO (My University, 2010)
Most ontology mapping research has focused on the matching of ontologies written in the same natural language, and developing tools and techniques that support this monolingual ontology mapping process. However, as knowledge modelling is not restricted to the usage of a single natural language, mapping systems must be able to operate upon ontologies that are labelled in diverse natural languages. This paper outlines a semantic-oriented cross-lingual ontology mapping framework that makes use of several information sources to influence the selection of ontology label translations in the process of generating high quality mapping results, and presents a high-level overview of the evaluation strategy of the proposed framework.
EKAW 2010 - Knowledge Engineering and Knowledge Management by the Masses
PUBLISHED
Lisbon, Portugal
Keywords: Cross-Lingual Ontology Mapping; Appropriate Ontology Label Translation; Multilingual Ontologies; Information engineering